Students’ Difficulties in Learning English and the Solutions: Case Study of Students of Sunan Kalijaga State Islamic University : English - Ahmad Asroni (Prodi Tadris Bahasa Inggris, 2023)
This article discusses students’ difficulties in learning English and the solutions by studying of students of Sunan Kalijaga State Islamic University, Yogyakarta. English is being treated as a world language because of its vast presence all over the world. Nevertheless, achievement of quality of learning English in Indonesia is still stagnant. One of the indicators is the students lack of mastering English. A lot of students still consider English as one of the most difficult subjects. This situation, of course, will influence the students learning process. Indonesian students consequently are asked to learn English through the mastery of the four skills, but it is not easy to master them well because the students encounter many difficulties in learning English. Such difficulties are also faced by most of students of UIN Sunan Kalijaga. This is a field research based on qualitative data. The object of research is students of UIN Sunan Kalijaga Yogyakarta. In gathering the data, I distribute a simple questionnaire to UIN Sunan Kalijaga students. The results of this study found that according to most of UIN Sunan Kalijaga students, among four English skills, listening is the most difficult skill in learning English. Speaking places as second position. Next, writing places as third position. The last is most difficult skill placed by reading. There are many efforts done by UIN Sunan Kalijaga students to solve their difficulties in English. They are: (a) the students deepen English by joining English course institutions; (b) the students get accustomed to use English either speaking, writing, listening, or reading; (c) the students study English more seriously; (d) the students memorize English vocabulary as much as possible; (e) the students frequently consult with their teachers regarding English; (f) the students practice English frequently, (g) the students frequently attend English lecture; (h) the students get accustomed to watch English movies and listen English songs. (i) the students frequently ask to their friends and relatives or anyone understanding English. The solutions that can be offered to overcome difficulties in learning English. They are: (a) speak without fear; (b) use all of our resources; (c) surround ourself with English; (d) listen to native speakers as much as possible; (e) watch English films and television; (f) listen to English musics; (g) study as often as possible; (i) do exercises and take tests; (j) record ourself; and (k) listen to English. Besides, there are some solutions regarding English learning process. They are: avoid formality and prioritize quality; design English learning program clearly; teach English skills, not components of English; create a conducive English learning envorinment; motivate the students to study hard; and communicate with the students.